Early externalizing behavior problems: toddlers and preschoolers at risk for later maladjustment - Campbell, S B; Shaw, D S; Gilliom, M (Development and psychopathology, 2000)
The early emergence and developmental implications of externalizing behavior problems in toddlers and preschoolers are discussed with an emphasis on which young children are truly at risk for continuing problems. The extant literature is reviewed with a focus on the stability of early externalizing behavior and the diverse pathways that young children, primarily boys, with early-emerging problems may follow. Findings from a number of studies, both epidemiological and high risk, suggest that the small subgroup of boys with multiple risk factors that include especially high levels of early hyperactivity and aggression, and high levels of negative parenting and family stress, are most likely to evidence continuing problems at school entry. Sociodemographic and neighborhood influences are also discussed, as are implications for future research and policy.